2022
DOI: 10.7554/elife.76183
|View full text |Cite
|
Sign up to set email alerts
|

FER-mediated phosphorylation and PIK3R2 recruitment on IRS4 promotes AKT activation and tumorigenesis in ovarian cancer cells

Abstract: Tyrosine phosphorylation, orchestrated by tyrosine kinases and phosphatases, modulates a multi-layered signaling network in a time- and space-dependent manner. Dysregulation of this post-translational modification is inevitably associated with pathological diseases. Our previous work has demonstrated that non-receptor tyrosine kinase FER is upregulated in ovarian cancer, knocking down which attenuates metastatic phenotypes. However, due to the limited number of known substrates in the ovarian cancer context, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…The role of FER kinase as an independent prognostic factor was investigated in breast cancer where elevated FER levels correlate with high-grade breast cancer types. 14 Overexpression of FER is also associated with poor clinical outcomes in renal cell carcinoma, 15 non-small cell lung cancer, 16 lung adenocarcinoma, 17 ovarian cancer cells, 18 and hepatocellular carcinoma. 19,20 Few genomic rearrangements involving FER kinase have been reported in the literature to date.…”
Section: Discussionmentioning
confidence: 99%
“…The role of FER kinase as an independent prognostic factor was investigated in breast cancer where elevated FER levels correlate with high-grade breast cancer types. 14 Overexpression of FER is also associated with poor clinical outcomes in renal cell carcinoma, 15 non-small cell lung cancer, 16 lung adenocarcinoma, 17 ovarian cancer cells, 18 and hepatocellular carcinoma. 19,20 Few genomic rearrangements involving FER kinase have been reported in the literature to date.…”
Section: Discussionmentioning
confidence: 99%
“…IRSs can activate PI3K/Akt signalling downstream of the insulin-like growth factor receptor to promote tumour growth. [40][41][42] In trastuzumab-resistant breast cancer, IGF2/IGF-1R/IRS1 signalling has been demonstrated to be signi cantly activated via disruption of FOXO3a-miRNA negative feedback inhibition, providing a predictive biomarker and potential treatment strategy to overcome Herceptin resistance. 43 In ductal carcinoma in situ, high IRS1 with low IRS2 expression could predict the responsiveness and effectiveness of chemotherapy in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…There is contradiction in the literature regarding the regulation of CatSper by PKA. The group of Orta suggested that CatSper is regulated by PKA [ 65 ], whereas the group of Wang claim that CatSper is not activated by PKA [ 66 ]. We claim that CatSper is regulated/inhibited by Fer which is localized downstream to PKA (see model Figure 2 ), suggesting that PKA regulates CatSper indirectly via activation of Fer which inhibits CatSper.…”
Section: Oxidative Stress and Male Infertility: Current Knowledge Of ...mentioning
confidence: 99%